When Personalized Gamification meets Computing Education: A Multidimensional Approach to Motivate Students to Learn - Rodrigues, Luiz; Isotani, Seiji (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2023: Anais do XXXVI Concurso de Teses e Dissertações, 2023)
Computing Education (CE) is associated with motivational issues, which might lead to poor performance and dropouts. Whereas gamification might tackle motivational issues, it must be personalized to both user and contextual characteristics to achieve its full potential. However, most guidelines for personalizing gamification are limited to a single user dimension, and the few that go beyond that limitation lack empirical evaluations comparing them to the standard, one-size-fits-all (OSFA) approach. Hence, in the context of CE, this thesis developed and validated an approach for personalizing gamification designs of educational systems to contextual and user characteristics. As results, we generated 10 studies, two recommender systems, two datasets, a number of assessments/quizzes on CE, and data analysis plans. Those contributions might solve the issues of OSFA gamification, posing multidimensional personalization of gamification - based on both user and contextual dimensions - as the new state of the art. Furthermore, our empirical evidence reveals a new perspective in which multidimensional personalization might address equity and inclusion issues in gamified learning. Thus, this thesis informs the design of gamified practices and provides research questions and materials for future studies.